Towards the development of remote work in Kazakhstan: the effectiveness of legislative opportunities - Kaishatayeva, А.К.; Bayazitova, Р.Т. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
Within the framework of modern challenges on a global and national scale, as well as the development of digital solutions, the issue of effective legal regulation of remote work is an important step towards the development of flexible forms of employment. A forced measure of organizing the labor process in Kazakhstan during the pandemic and riots was the use of the remote work format. In recent years, the legislation in the country in the field of remote work regulation has undergone significant changes, however, whether they are effective for the development of remote work in Kazakhstan is a question that needs to be considered. The purpose of this article is to study the norms of the labor legislation of the Republic of Kazakhstan in the field of remote work in terms of their effectiveness for the development of this format of organizing labor relations. The article demonstrates the factors that prompted the state to more detailed regulation of remote work, analyzes the conditions for the emergence of remote labor relations, labor conditions. At the same time, the problems of local regulation of labor relations in the field of remote work are considered with consideration of empirical material in the form of collective agreements of some Kazakhstani organizations. The study proposes recommendations aimed at the effective regulation of telecommuting. Understanding the current state of the possibilities of applying legislative aspects in practice is a key component to the further development of recommendations for improving the tools for the legal organization of remote work. The conducted studies are aimed at expanding knowledge in the field of legal aspects of regulation of remote work, as well as demonstrating the experience of Kazakhstan in the development of remote work.